2012
DOI: 10.1016/j.eplepsyres.2011.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin gene polymorphisms and psychiatry comorbidities in temporal lobe epilepsy

Abstract: INTRODUCTION: Among epileptic patients, those with temporal lobe epilepsy (TLE) are at risk to develop psychiatric disorders. Evidence suggests that the association of psychiatric disorders with epilepsy might be related to common biological substrates. Studies support that serotonin (5-HT) may also contribute to a predisposition to epilepsy. The 5-HTTLPR and 5-HTTVNTR polymorphisms in the 5-HTT gene and the C-1019G polymorphism in the 5-HT1A gene have been studied in psychiatric diseases. As far as we know, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 43 publications
2
12
0
2
Order By: Relevance
“…In the present study C-carriers display the largest context-FPS and the largest cue-FP-VAS. This may appear contradictory, but C-carriers demonstrated higher amygdala reactivity in an imaging study (Fakra et al, 2009) and increased risk for anxiety disorders in patients with temporal lobe epilepsy was found in C-carriers (Schenkel et al, 2012). As has been argued for other polymorphisms, speaking of an allele that confers just 'risk' may not accurately describe the different effects the 5-HTR 1A polymorphism under study (Beste et al, 2011).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In the present study C-carriers display the largest context-FPS and the largest cue-FP-VAS. This may appear contradictory, but C-carriers demonstrated higher amygdala reactivity in an imaging study (Fakra et al, 2009) and increased risk for anxiety disorders in patients with temporal lobe epilepsy was found in C-carriers (Schenkel et al, 2012). As has been argued for other polymorphisms, speaking of an allele that confers just 'risk' may not accurately describe the different effects the 5-HTR 1A polymorphism under study (Beste et al, 2011).…”
Section: Discussionmentioning
confidence: 91%
“…Also, G-carriers of this polymorphism were shown to have higher neuroticism and related personality traits (Strobel et al, 2003). In contrast, increased amygdala activity (Fakra et al, 2009) and risk for anxiety disorders in patients with temporal lobe epilepsy (Schenkel et al, 2012) were reported in C-carriers of this 5-HTR 1A polymorphism. Based on all these findings, variability in the regulation of contextual anxiety through different functionality of the serotonin 1 A receptor may contribute to individual differences in contextual responding, as discussed above.…”
Section: Introductionmentioning
confidence: 93%
“…However, surprisingly, a study found a more homogeneous ancestry throughout Brazil than previously estimated, with 60-78% being of European background [26]. In addition, the south and southeast regions of Brazil present a higher percentage of European ancestry, as already discussed previously [27].…”
Section: Discussionmentioning
confidence: 55%
“…The heterogeneity of the group in terms of the type of PD might have interfered with our results. However, it is also possible that other mechanisms that are related to 5-HT are correlated with the presence of PD, such as altered serotonin receptor or transporter functions (Drevets et al, 1999;Hasler et al, 2007;Hung et al, 2011;Sargent et al, 2000;Schenkel et al, 2011). Nonetheless, other mechanisms (Gattaz et al, 2011;Kandratavicius et al, 2013b) are also probably related to these findings.…”
Section: Discussionmentioning
confidence: 68%